Cooperative Jahn–Teller phase transition of icosahedral molecular units. (21st December 2016) - Nasrollahi, Seyed H; Vvedensky, Dimitri D
Abstract: Non-linear molecules undergo distortions when the orbital degeneracy of the highest occupied level is lifted by the Jahn–Teller effect. If such molecules or clusters of atoms are coupled to one another, the system may experience a cooperative Jahn–Teller effect (CJTE). In this paper, we describe a model of how the CJTE leads to the crystallization of the disordered phase. The model Hamiltonian is based on a normal mode decomposition of the clusters in order to maintain the symmetry labels. We take account of the electron-strain and the electron-phonon couplings and, by displacing the coordinates of the oscillators, obtain a term that explicitly couples the Jahn–Teller centers, enabling us to perform a mean-field analysis. The calculation of the free energy then becomes straightforward, and obtaining phase diagrams in various regimes follows from the minimization of this free energy. The results show that the character of the phase transition may change from strong to weak first order and even to second-order, depending on the coupling to the vibrational modes. Taken together, these results may serve as a paradigm for crystallization near the transition temperature, where the atoms tend to form clusters of icosahedral symmetry.